Stability enhancement of inverter dominated power systems using virtual inertia control - Subramanian, Lalitha (Nanyang Technological University, 2021)
The electric power system has been traditionally energized by synchronous machines like steam turbines, hydro turbines, and diesel engines. These rotating machines inherently contribute to the system's resilience by providing rotational inertia. The grid frequency is indicative of the real-time power balance across the grid and can be treated as one of the primary grid health indices. On the occurrence of a fault, inertia helps the frequency to gradually deviate from the nominal value, i.e. the higher the amount of inertia, the slower is the rate of frequency deviation. The presence of adequate inertia, therefore, provides the liberty of allowing a control delay for the governor-input valve controls to respond to the frequency deviation. With the displacement of synchronous machines by converter-connected distributed intermittent renewable sources such as solar photovoltaics (PV) and wind turbine systems, the reduction of inherent system inertia is evident. However, there is also a counterpoised observation that the required amount of inertia in the transformed power system is reduced, given the faster response of the converter-based distributed energy resources (DERs). Therefore, the solution is to resort to synthetic inertia to improve the resilience of the power system, or to faster primary frequency response to improve the system reliability with the limited resilience of a low-inertia grid. In this context, this thesis explores questions such as: What is the adequate synthetic inertia/ frequency response capability for a stable power system? How can one quantify the flexibility required to provide this adequate inertia? Does synthetic inertia greater than the adequate level necessarily indicate a higher stability margin? How different is the effect of distributed synthetic inertia on oscillatory stability compared to synchronous inertia? Firstly, the aspects of flexibility and methods to characterize them for adequate synthetic inertia and fast-frequency response are addressed. A generalized virtual storage flexibility model has been proposed to quantify the heterogeneous bidirectional flexibilities and their combination to provide a certain level of synthetic inertia. As an illustration, a hybrid energy storage system has been sized for synthetic inertia and fast frequency response provision in an isolated power system. The subsequent chapters discuss synthetic inertia and fast-frequency control actuated by PV systems with hybrid energy storage. In this thesis, inverter control has been explored with a complete DC-side model taking into account the effects of PV intermittency, unlike most research works on inverter control that assume a sufficiently large DC source/sink. Synthetic inertia controllers are categorized as grid-following and grid-forming topologies, which significantly affect their impact on system stability. Conventionally, the inertia and damping parameters are tuned and fixed over a scheduled time slot based on the available flexibility. It has been identified that higher inertia is required on the occurrence of a disturbance to limit the rate of frequency deviation and higher damping is required for a faster settling time. Therefore, for each of the control topologies, a rule-based real-time inertia tuner has been proposed to optimize the frequency deviation, its rate, and settling time. The algorithm has been improved through a model predictive control with a rate-based linearization. The rate-based linearization extends the model validity to the transient zones. For systems with multiple grid-formers and multiple frequency responsive units, a distributed optimization problem has been formulated and solved to collectively tune the inertia and damping parameters that are constrained by the available flexibilities. The efficacy of distributed grid-forming and grid-following synthetic inertia in replacing their synchronous counterpart in a microgrid has been compared. Microgrid regulation in grid-connected and islanded modes has been studied by modeling the DERs with discussed control strategies. The impact of the two types of synthetic inertia controls on the small-signal stability of the system is examined by modal analysis and bifurcation plots to derive the conditions for oscillatory stability in a microgrid with distributed synthetic inertia reserves. The effectiveness of the proposed control strategies in restoring the frequency stability of low-inertia systems has been validated by power hardware-in-the-loop experimentation.